Microangiopathic Hemolytic Anemia: A Rare Clue to Diagnose Bone Marrow Metastatic Gastric Adenocarcinoma (Journal of Medicine, 2019)
Microangiopathic Hemolytic Anemia (MAHA) is a hematological condition which is very rare for the primary presentation of a gastric adenocarcinoma with bone marrow metastases. When it emerges as initial findings in a previously undetected case of malignancy, the diagnosis is often missed and results in inappropriate management. Carcinoma stomach associated with MAHA is generally having fulminant course. This is a case report of a 30-year-old male who presented with widespread bone marrow infiltration along with Coomb’s negative haemolytic anemia, thrombocytopenia and schistocytes in peripheral blood typical of MAHA. The combination of MAHA and bone marrow infiltration in gastric adenocarcinoma is a very rare entity. When the cause of progressive MAHA is unknown, the possibility of cancer-associated MAHA must be excluded by performing additional tumor workup, including the detection of tumor markers, Endoscopy of upper GIT, colonoscopy, bone marrow examinations, and PET-CT or bone scans.J MEDICINE JUL 2019; 20 (2) : 102-105